BE_VERWALTUNGSGERICHT 100 2018 244 vom 6. Dezember 2019 - BE Verwaltungsgericht (2019)
Strassenplan \"Neubau Fussgängerquerungen Seestrasse\" (RRB Nr. 753/2018 vom 27. Juni 2018; 32.08-17.10) | Nutzungspläne